2013
DOI: 10.1089/ars.2012.4677
|View full text |Cite
|
Sign up to set email alerts
|

An Indole Derivative Protects Against Acetaminophen-Induced Liver Injury by Directly Binding to N-Acetyl-p-Benzoquinone Imine in Mice

Abstract: Aims: Acetaminophen (APAP)-induced liver injury is mainly due to the excessive formation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) through the formation of a reactive intermediate, N-acetyl-pbenzoquinone imine (NAPQI), in both humans and rodents. Here, we show that the indole-derived synthetic compound has a protective effect against APAP-induced liver injury in C57Bl/6 mice model. Results: NecroX-7 decreased tert-butylhydroperoxide (t-BHP)-and APAP-induced cell death and ROS/RNS for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…These findings demonstrated that WZ successfully rescued mice from APAP hepatotoxicity and might provide clinically useful means to treat liver injury associated with APAP. NAC had no therapeutic effect on APAP hepatic toxicity when administrated 4 hours after APAP challenge, which was consistent with previous studies (James et al, 2003;Park et al, 2013). Several studies have demonstrated that NAC prevented APAP toxicity when administered before or early (such as 1 or 2 hours) after APAP (Salminen et al, 1998;James et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…These findings demonstrated that WZ successfully rescued mice from APAP hepatotoxicity and might provide clinically useful means to treat liver injury associated with APAP. NAC had no therapeutic effect on APAP hepatic toxicity when administrated 4 hours after APAP challenge, which was consistent with previous studies (James et al, 2003;Park et al, 2013). Several studies have demonstrated that NAC prevented APAP toxicity when administered before or early (such as 1 or 2 hours) after APAP (Salminen et al, 1998;James et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…Numerous studies have revealed a role for mitochondrial ROS in the activation of inflammatory signaling pathways to stimulate the production of proinflammatory cytokines, such as TNF, IL6, and IL1B [4,24,25]. Thus we pretreated BMDMs with the mitochondrial-targeted antioxidant MitoTEMPO [26] or NecroX [27] during infection with Mtb or BCG. As shown in Figure 3(g), treatment of BMDMs with MitoTEMPO or NecroX significantly inhibited the Mtbinduced generation of proinflammatory cytokines, including TNF, IL6, IL1B, and CXCL5, in sirt3 −/and Sirt3 +/+ BMDMs in a dose-dependent manner.…”
Section: Accumulation Of Dysfunctional Mitochondria and Increased Oxidative Stresses Leads To Excessive Inflammation In Sirt3 Deficiency mentioning
confidence: 99%
“…Recently, one member of this group of compounds, NecroX-7, was shown to inhibit formation of mitochondria-specific ROS/reactive nitrogen species in H9C2 cells and hepatocytes after induction by tert-butyl hydroperoxide or doxorubicin (24,25). NecroX-7 has also been used as an antidote to acetaminophen toxicity (26) and exerts a protective effect by preventing the release of HMGB1 in ischemia/reperfusion injury (27). The ability of NecroX-7 to protect cells and cellular components against oxidative stress and HMGB1 provided a rationale for its use in preventing GVHD induction in the setting of allogeneic HSCT.…”
mentioning
confidence: 99%